Grubs Up: Multiple Enactments of Insects as Food in Aotearoa/New Zealand: (SAANZ postgraduate essay prize ‘highly commended’ 2021) - Hyde, Caitlin (New Zealand Sociology, 2022)
In response to growing environmental concerns and food security pressures, the idea of eating insects is gaining traction around the world. However, despite being a sustainable and nutritious source of protein, eating insects remains largely taboo in the West. A small market for edible insects exists in Aotearoa/New Zealand but the practice is not widespread and the industry is struggling to expand. This article draws on material semiotic theory, specifically the concept of enactment, to encourage consideration of edible insects as not singular, but multiple. This analysis provides some insight into how insects are ‘becoming food’ (or not) across different venues in Aotearoa, both in the sense of initial edibility and routine consumption.